Achieving employee engagement through effective internal communication - Senelisiwe Mbhele; Estelle de Beer (Communicare)
Internal communication is a prerequisite for organisational success as it underpins organisational effectiveness. Previous research (Albrecht, 2010; Andrew & Sofian, 2012; Hayase, 2009; Mamdoo, 2012; Markos & Sridevi, 2010; Meng & Berger, 2012; Ruck & Welch, 2012; Welch & Jackson, 2007; Welch, 2011) has linked this process to employee engagement, which generally refers to “a positive fulfilling, work-related state of mind that is characterised by vigour, dedication and absorption.” To illustrate how employee engagement can be achieved through internal communication, a quantitative research approach was used to obtain data from a sample of 300 respondents identified by means of systematic random sampling from a population of 1 322 employees from the case organisation. The findings point to the critical role played by internal communication in the achievement of employee engagement and specifically investigated the relationship between employee engagement and constructs such as: participative organisational culture; supportive communication climate; participative leadership communication; quality and reliability of information; two-way asymmetrical communication and two-way symmetrical communication.